Cottus specus, a new troglomorphic species of sculpin (Cottidae) from southeastern Missouri. - Adams, Ginny L.; Burr, Brooks M.; Starkey, David E. (Zootaxa, 2013)
Cottus specus, a new species, is described from the karst regions of the Bois Brule drainage in eastern Missouri, USA. Cottus specus is distinguishable from all members of the genus Cottus using both genetic and morphological characters, including eye size and cephalic pore size. Cottus specus represents the first description of a cave species within Cottus. The addition of C. specus brings the total number of recognized species of Cottus to 33 in North American fresh waters.